Field, light and food: adapting the town square as a leisure gathering space at night - Zakariya, Khalilah; Harun, Nor Zalina; Mansor, Mazlina (Malaysian Institute of Planners, 2017)
A square is an important built open space in cities and towns. In many urban areas throughout the world squares act as essential form of public space, making them a venue where socializing, meeting and event activities take place. Over the years, more squares are emerging as public spaces in Malaysian cities and towns as an alternative to parks. While most people often visit parks in the morning and evening, they still need a public space where they can conduct their leisure activities after working hours and at night. This is particularly relevant for towns and cities located in tropical and humid countries like Malaysia. The rising need to be outdoors in a cooler environment in the evening and at night, as a respite from the daytime heat and work, has attracted people back to the town squares. The sense of openness that a square offers is different from that of a park at night. The attractiveness of a square as a night space relies on how its users relate to the square’s physical, social and environmental attributes. Through examining a town square in Malaysia that has transformed into an active public space at night, this article aims to explore the attributes that enabled the square to be adapted into a night space. The findings revealed that there is a strong relationship between the opportunities for various activities and the provision of relevant infrastructure that support the square to serve as a public space for people at night. This is an important tangent in shifting how urban public space in Malaysia might be designed and planned in the future so as to cater for the changing needs of urban dwellers.